Brassica oleracea var. capitata: extração, caracterização química e atividade biológica de metabólitos secundários - Dal Prá, Valéria (2013)
The main objective of this work was to evaluate the antioxidant and antibacterial activities of extracts of Brassica oleracea var. capitata, obtained by supercritical CO2 and ultrasound-assisted extractions, as well as to carry out the characterization of these extracts using gas chromatography coupled with mass detector. For supercritical CO2, five extractions were performed to investigate the influence of pressure (10-25 MPa) and temperature (20-60°C) on the extraction yield, chemical composition and antioxidant activity towards peroxyl, superoxide and hydroxyl radicals. The highest extraction yield was 0.47% at 60 °C and 25 MPa. In the characterization of the extracts was possible to identify compounds like sulforaphane and iberin nitrile. All extracts showed antioxidant activity for the three radicals, although the highest activity for all radicals was obtained using the extract obtained at 60 °C and 25 MPa (run 2). For the ultrasound-assisted extraction were evaluated the effects of solvent concentration and temperature. The extracts obtained in the optimized extraction condition, were subjected to different hydrolysis conditions before use in biological assays. It was evaluated the antioxidant activity against DPPH, superoxide and peroxyl radicals, besides the antibacterial activity against S. aureus and E. coli. Both crude and hydrolyzed extracts were characterized by gas chromatography coupled with mass detector. The best condition for extraction was 30 ° C and 60% (w /v) of ethanol. All extracts showed antioxidant activity towards DPPH, superoxide and peroxyl radicals, but the use of hydrolyzed extracts improved considerably the antioxidant activities. Antibacterial activity was detected only in extracts hydrolysates Brassica oleracea var. capitata. The main contributions of this work were that the use of supercritical CO2 extraction to obtain bioactive compounds from Brassica oleracea var. capitata showed a promising alternative to conventional methods of extraction, since it allowed the extraction of compounds of interest in science and industry. Besides, in this work was demonstrated that the hydrolysis of extracts can increase the antioxidant activity of plant extracts.